2022
DOI: 10.5751/es-12918-270114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pastoral traditional ecological knowledge: a global state-of-the-art review

Abstract: Traditional ecological knowledge enables pastoralists to cope with social-ecological changes, thereby increasing the sustainability of their practices and fostering social-ecological resilience. Yet, there is a significant knowledge gap concerning the extent to which pastoral traditional ecological knowledge has changed over time at the global level. We aim to fill this gap through a systematic literature review of 288 scientific studies on pastoral traditional ecological knowledge. We reviewed 152 papers in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…On the other hand, we showed that introducing numerous SWI can change livelihood strategies, anchoring local communities to the proximity of water points, especially in places with favorable agro-climatic conditions. Our findings support the position that maintaining mobility is fundamental for pastoralists to cope with drought conditions 74 and fostering long-term resilience 75,76 .…”
Section: Insights For Resilient Water Infrastructure Development In D...supporting
confidence: 80%
“…On the other hand, we showed that introducing numerous SWI can change livelihood strategies, anchoring local communities to the proximity of water points, especially in places with favorable agro-climatic conditions. Our findings support the position that maintaining mobility is fundamental for pastoralists to cope with drought conditions 74 and fostering long-term resilience 75,76 .…”
Section: Insights For Resilient Water Infrastructure Development In D...supporting
confidence: 80%
“…Ethnobotanical research conducted by ethnographers often focuses on medicinal and wild food plants. However, more research on traditional and local knowledge of livestock-animal relations to forage and fodder plants will be needed in the future (Sharifian et al 2022a, 2022b). We raise the hypothesis that early ethnographic data were most probably collected during in-door interviews, as indicators relevant on pastures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Pastoralists' lifetime experience and daily monitoring of changes in the landscape enable them to give important overall impressions based on their local knowledge (Fernández‐Llamazares et al 2021; Gantuya et al 2021; Sharifian et al 2022). Compared to P. juliflora , local pastoralists in Minab and Bandar Abbas sites clearly perceived P. cineraria as having a lower colonizing ability (potential for invasion), and to be much better for local ecosystem services and livelihoods.…”
Section: Discussionmentioning
confidence: 99%